DYNAMICS OF HIGHGER MENTAL FUNCTION IN PATIENTS WITH OBLITERATING LESIONS OF INTERNAL CAROTID ARTERIES IN SURGICAL BRAIN REVASCUL - R. A. Vinogradov; L. V. Timchenko; A. N. Torgashova; K. A. Bondarovich; T. I. Kаpran; V. V. Seledtsov (Неотложная медицинская помощь)
Obliterating atherosclerosis of internal carotid arteries is one of the main causes of ischemic stroke and discirculatory encephalopathy. It causes up to 40% of ischemic disorders of cerebral circulation. Currently, the strategy for stroke prevention is determined by the intensive development of surgical methods of treatment, primarily methods for managing lesions of brachiocephalic arteries. Based on the results of a number of international multicenter randomized studies, indications for reconstructive operations for BCA, tactics for managing patients in the postoperative period were formulated. A number of patients with atherosclerotic lesions of brachiocephalic arteries have reduced cognitive functions. The aim of the study is to compare cognitive functions (CF) in patients who underwent different surgical approaches in the treatment of obliterating atherosclerotic lesion of internal carotid arteries (ICA).MATERIAL AND METHODS. We studied higher mental functions (HMFs) in 116 patients with obliterating unilateral or bilateral lesion of ICA. The study of cognitive functions (MF) was performed prior to carotid endarterectomy (CE, group 1, n=73) and transluminal balloon angioplasty of ICAs (TBA of ICA, group 2, n=43), and on days 5–7 and 30–31 after cerebral revascularization (CR). To assess the overall severity of cognitive impairment, the summary indicators of main screening neuropsychological tests were used: MMSE; MoCA; Frontal Assessment Battery (FAB); Beck Depression Inventory and Hamilton Depression Rating Scale.RESULTS. Results Neuropsychologic disorders were reavealed in 98% of patients prior to surgery. An initially comparable condition of HMF in groups with CE and TBA of ICA was revealed. MMSE2 revealed a significant improvement in the results in group 1 both in comparison with the initial data (p<0.05) and in comparison with the results of the second test of group 2. The results of MMSE1 and MMSE2 in group 2 did not show significant differences (p>0.05). MMSE3 showed a significant improvement in the test results in each group compared to MMSE1 and MMSE2. MMSE3 results were significantly better (p<0.01) in group 1 than in group 2. MoCA revealed most significant differences in group 1 results with a significant decrease in cognitive dysfunction both in MoCA1, MoCA2, MoCA3 either within the group (p><0.05) or compared to MoCA3 data between CE group and TBA group (p><0.01). FAB showed that the FAB2 test amounted to 16.2 points in the group with CE and 14.6 points in the group with TBA of ICAs (p><0.05). A significant improvement in the performance of mnestic functions was noted when examining patients in the dynamics of FAB3: 17.3 and 15.6 points (p><0.05), respectively. According to Hamilton Depresion Rating Scale and Beck Depression Inventory, both groups of patients showed a moderate level of anxiety and depression (12.4 and 15.8 according to Hamilton Depression Rating Scale (p><0.05), 12.3 and 14.4 according to Beck Depression Inventory (p>0.05)). During the second test, the depressive mood of patients was reduced (on the Hamilton scale 8.4 and 13.8 points.CONCLUSION When comparing HMFs in patients who underwent a different surgical approach (CE vs TBA of ICAs) in the treatment of obliterating atherosclerotic lesions of ICAs, we found that: 1) the maximum improvement in HMFs appears by the 30th day of the postoperative period in comparison with preoperative parameters; 2) the most significant improvement HMFs test parameters by the 30th day of the postoperative period is noted in the group where CE was used as the method of surgical revascularization of the brain.